ANALISIS IMPLEMENTASI APLIKASI SISTEM INFORMASI PEMERINTAHAN DAERAH (SIPD) TERHADAP PENGELOLA KEUANGAN PADA KANTOR KECAMATAN MUARA JAYA KABUPATEN OKU - Wantutri, Wisterlin; Anwar, Yuniarti; Wiralaga, Harby R. (Journal Economics Technology And Entrepreneur, 2025)
This study is entitled "Analysis of the Implementation of the Regional Government Information System (SIPD) Application for Financial Management at the Muara Jaya District Office, OKU Regency." The purpose of this study is to determine the implementation or application of the Regional Government Information System Application for Financial Management at the Muara Jaya District Office, OKU Regency, with several indicators such as Budget Planning (Strategic Plan Preparation, Work Plan Preparation, and Budget Preparation), Implementation and Administration (Budget Implementation Document Preparation, Cash Budget Plan Preparation, Payment Request Preparation, Payment Request Preparation, and Expenditure Administration), Accounting and Financial Reporting (Budget Realization Report, Budget Balance Change Report, Operational Report, Equity Change Report, Balance Sheet, Prognosis, Journal Book, and General Ledger). The study concluded that the implementation of the Regional Government Information System (SIPD) at the Muara Jaya District Office, Ogan Komering Ulu Regency, was deemed ineffective and poorly implemented. This was due to the system being relatively new, imperfect, still under development, and the presence of technical constraints. Therefore, SIPD needs to be updated or upgraded to become a better application in the future. The suboptimal implementation of SIPD experienced by the Muara Jaya District Office, Ogan Komering Ulu Regency, occurred in the presentation of Regional Financial Information.